Re-engineering of Manufacturing Parts by Computed Tomography Data - Akdogan, Anil; Vanli, Ali Serdar; Durakbasa, Numan (SPRINGER-VERLAG BERLIN, 2019)
The number of computed tomography (CT) applications today is satisfactorily high and rapidly increasing in many environments. Many manufacturing industries use CT technologies. In order to able to reach very accurate internal dimensions even at complicated workpieces to achieve the internal structure of a manufactured object is one of the main advantages of the system. Its' non-destructive style, comparison capability with reference models and extremely high attribute imaging are the other issues. In this paper, CT systems, scanning capabilities and technological developments is examined in the frames of the latest technology and future CT technologies. It especially gives the latest information about inspectable materials and application examples of manufacturing industries. Because innovative design and development works of industrial products in manufacturing environments require valuable big data. The conducted experimental CT results were used for re-engineering applications for continuous improvement of the manufacturing process. The results were also valuable for quality control and sustainable quality assurance.
Keywords: Computed tomography; Re-engineering; Manufacturing; Casting; Quality control; Engineering